Strategi Partai Sira Sebagai Partai Lokal Dalam Menghadapi Tantangan Pasca Pemilukada - Nofriadi, Nofriadi; Islami, Naufal; Alfarizzi, Muhammad; Amanda, Cut Rahel; Izzani, Maghfirah; Anisa, Tiara (Universitas Muara Bungo, 2025)
Political parties are one of the crucial instruments in the democratic system in Indonesia, the Independent Solidarity of the Aceh People (SIRA) party is a local political party in Aceh that faces political challenges after regional elections and general elections. The main focus in this paper is to understand the Independent Solidarity Party of the Aceh People (SIRA) how this party can maintain its name and expand its political influence in the highly competitive party system in Indonesia, with the political, mobilization, and communication approaches that have been carried out by the SIRA Party in the context of competition at the local political level post-conflict and post-Helsinki MoU. In this study, a qualitative approach was used with a case study method. The collection of research data was collected from the results of in-depth interviews with the Secretary General of the DPP of the SIRA Party, through field observations, and interviews. The results of the study found that the SIRA party uses various strategies by emphasizing more on strengthening young cadres, collaborating with regional elites. Although in the 2024 general election the SIRA party failed to get a seat in the DPRA because it focused on nominating regional heads, from this strategy it succeeded in giving the party chairman to become the deputy regent of Nagan Raya. The conclusion of this study is that the SIRA Party shows high adaptability through various strategies such as locally-based and community-based politics, but the SIRA Party also faces great challenges such as limitations in funding sources, low participation of the millennial generation and lack of use of digital technology. The limitation of this study lies in the limited scope of informants and has not met the perspectives of sympathizers or voters.